174k views
0 votes
Solve the system of equations.
​ 7x−3y=20
y=5x−4
x=
y=


2 Answers

5 votes

Answer:

x = -1, and y = -9

Explanation:

This is done by solving one of the two equations for x or y, then substituting it in place of that variable in the other equation.

Since y is already clearly defined in the second equation let's go with that:


Given\ 7x - 3y = 20,\ and\ y = 5x - 4


7x - 3(5x - 4) = 20


7x - 15x + 12 = 20


7x - 15x = 20 - 12


-8x = 8


x = -1

Now we can replace x in the equation for y with -1:


y = 5(-1) - 4


y = -5 - 4


y = -9

To make sure our answers are correct, let's substitute them into the original equations:


(-9) = 5(-1) - 4\\-9 = -5 - 4\\-9 = -9

Good, let's test the other equation


7(-1) - 3(-9) = 20\\-7 - (-27) = 20\\-7 + 27 = 20\\20 = 20

So we know that our answer is correct.

User Bendemann
by
6.1k points
6 votes

Answer:

Explanation:

substitute the value of y in the first equation.

7x-3(5x-4)=20

7x-15x+12=20

-8x=20-12

x=8/-8

x= -1

then you substitute the value of x on the y equation to find y

y=5×-1 -4

y= -5-4

y= -9

User Zout
by
5.9k points